Analisis Usability Pada Aplikasi Allo Bank Menggunakan Heuristics Evaluation - Utami, Melida Ratna; Setiawan, Ito (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Allo Bank is a digital banking service available in Indonesia. The Allo Bank application has received low reviews on the Google Play Store. Based on several comments, it is known that the application does not function well, frequently experiences errors, and users face difficulties when making payments. Additionally, the application often cannot be used due to problems whose causes are unknown. This study aims to determine the level of usability of the Allo Bank application and identify which principles are not met based on the Heuristics Evaluation principles. The Heuristic Evaluation method was used for this research, while data was collected using questionnaires, and the sampling technique employed was the Slovin technique. The results of this research indicate that the usability of the Allo Bank application falls into the